Wind variability in the Canary Current during the last 70 years - Marrero Betancort, Nerea; Marcello, Javier; Rodríguez Esparragón, Dionisio; Hernández-León, Santiago (Ocean Science, 2020)
Climate evolves following natural variability, and knowledge of these trends is of paramount importance to understand future scenarios in the frame of global change. Obtaining local data is also of importance since climatic anomalies depend on the geographical area. In this sense, the Canary Current is located in one of the major eastern boundary current systems and is mainly driven by the trade winds. The latter promote Ekman transport and give rise to one of the most important upwelling zones of the world on the northwest African coast. Nearly 30 years ago, Bakun (1990) raised a hypothesis contending that coastal upwelling in eastern boundary upwelling systems (EBUSs) might be intensified by global warming due to the enhancement of the trade winds, increasing pressure differences between the ocean and the continent. Using available NCEP/NCAR wind data north of the Canary Islands from 1948 to 2017, we show that trade wind intensity experienced a net decrease of 1 m s-1 span classCombining double low line"inline-formula">-1 . Moreover, these winds are strongly influenced, as expected, by large-scale atmospheric patterns such as the North Atlantic Oscillation (NAO). In addition, we found a relationship between the wind pattern and the Atlantic Multidecadal Oscillation (AMO), indicating that the ocean contributes to multidecadal atmospheric variability in this area of the ocean with a considerable lag (<10years). 963 951 13 1,086 3,416 Q1 Q1 SCIE